Characterization of Rhizoctonia solani associated with root/collar rots and blights - and O.P. SHEORAN, S. SUNDER, H.R. KATARIA, SATYAVIR (Indian Phytopathology, 2003)
One hundred-twelve isolates of Rhizoctonia solani were collected from soil, root and collar rot or foliage blight infected plants from several locations in Haryana. Of these, 43% belonged to anastomosis group-1 (AG-1 lA, AG-1 IC), 37% to AG-4, 9% to AG-3 and 11% to AG-7. Studies on 20 selected isolates of different AGs revealed considerable variability in their cultural and morphological characters, growth and virulence. Sclerotia were large (1-4 mm) and produced in abundance in AG-1 IA but these were generally few and small in other AGs. Isolates of AG-7 had the narrowest (7.2 JJm)while those of AG-3 had the widest (9.0 JJm)hyphae. Wide variations were recorded in virulence among different AGs. Isolates of AG-1, AG-4 and AG7 were moderate to highly virulent on hypocotyls of mungbean and chickpea. Leaves of rice were severely infected by AG-1 lA, while AG-1 IC and AG-4 caused mild infection. Isolates of AG-3 failed to infect either group of hosts. It is the first report on occurrence of AG-7 in India.